Seaweed-Based Local Economic Development in Takalar District - Kasri, Kasri (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2022)
This research was conducted in April 2022. The location of this research was Laikang Village, Mangarabombang District, Takalar Regency. This type of research is a survey. Survey research is a method of collecting data in the form of a questionnaire, which is then disseminated to respondents. Answers from respondents in survey research allow researchers to be able to conclude, as well as generalize a population that is represented by the respondent. Sampling was done by purposive sampling. The samples used in this study were 30 seaweed cultivators. Research data collection was carried out by conducting interviews and distributing questionnaires to respondents. Data analysis used in this research is descriptive qualitative and quantitative. Descriptive analysis is a kind of data research that helps in describing, demonstrating, or helping to summarize data points so that patterns can be developed that satisfy all data conditions. The process of cultivating seaweed is also relatively easy and does not require too much money, so the Takalar coastal community develops this commodity as their main livelihood. In its development, the community experiences obstacles in developing commodities so that the community and government need to implement strategies to overcome problems faced by coastal communities such as increasing the quantity and quality of grass, establishing partnerships with companies and financial institutions, processing seaweed to increase added value, strengthening institutions seaweed cultivators, provide assistance with seaweed cultivation facilities and infrastructure, and supervise coastal areas.